1993
DOI: 10.1113/jphysiol.1993.sp019657
|View full text |Cite
|
Sign up to set email alerts
|

Identification of vagal sensory receptors in the rat lung: are there subtypes of slowly adapting receptors?

Abstract: SUMMARY1. We studied the characteristics of pulmonary sensory receptors whose afferent fibres are in the left vagus nerve of opened-chest rats. The activity of these receptors was recorded during mechanical ventilation approximating eupnoea, as well as during deflation, stepwise inflations and constant-pressure inflations of the lungs. Data were also collected from closed-chest rats and analysed separately.2. Ninety-four per cent of receptors were located in the ipsilateral lung or airways with the remainder i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
59
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 42 publications
6
59
3
Order By: Relevance
“…Similar types of afferent units of the vagus nerve in the same species have been reported by Bergren and Peterson (1993); they suggested that three categories of receptors, as suggested by Tsubone (1986), belong to slowly adapting pulmonary stretch receptors (SARs). Based on the difference between phasic firing patterns of SARs in both closed and opened chest rats, Bergren and Peterson (1993) classified four subtypes of SARs: inflationary, most inflationary, deflationary, and most deflationary. Wei and Shen (1985) also demonstrated four different types of SARs in rabbits, cats, and monkeys (i.e., phasic and tonic inspiratory units and phasic and tonic expiratory units).…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…Similar types of afferent units of the vagus nerve in the same species have been reported by Bergren and Peterson (1993); they suggested that three categories of receptors, as suggested by Tsubone (1986), belong to slowly adapting pulmonary stretch receptors (SARs). Based on the difference between phasic firing patterns of SARs in both closed and opened chest rats, Bergren and Peterson (1993) classified four subtypes of SARs: inflationary, most inflationary, deflationary, and most deflationary. Wei and Shen (1985) also demonstrated four different types of SARs in rabbits, cats, and monkeys (i.e., phasic and tonic inspiratory units and phasic and tonic expiratory units).…”
Section: Introductionmentioning
confidence: 58%
“…The deflationary SARs are specific types of myelinated vagal afferent fibers responding to lung deflation on airway collapse. The thickening of the airway smooth muscle is considered to act as an effective stimulus for deflationary SARs oriented in a perpendicular manner to the axis of the smooth muscle (Bergren and Peterson, 1993). The mechanism mediating the mechanical deformation of deflationary SARs has not yet been determined, but those receptors may have mechanosensitive channels on the endings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In series 4, suppressive effects of pretreatment with dimethylthiourea, N-acetyl-L-cysteine, 1.5 mg/kg HC-030031, 3.0 mg/kg HC-030031, AP18, vehicle 1, or vehicle 2 (the vehicle of HC-030031 or AP18) (each treatment: n ϭ 8) on 0% O 2 AIH-induced potentiation of the LVCF responses to injection of capsaicin were investigated in seven groups of rats. Additionally, the suppressive effects of pretreatment with dimethylthiourea, N-acetyl-L-cysteine, 3.0 mg/kg HC-030031, vehicle 1, or vehicle 2 (each treatment: n ϭ 8) on this potentiating response of AIH to ␣,␤-methylene-ATP was also evaluated in another five groups of rats. The LVCF responses to these chemical stimulants were measured at time points as described in series 1.…”
Section: Methodsmentioning
confidence: 99%
“…Only fibers that responded to capsaicin within 2 s after the injection were studied (12). Finally, the conduction velocity of the afferent fibers was measured, as described previously (3). Before the end of each experiment, the general locations of C fibers studied were identified within the lung structure by gently probing the tissues with use of a polyethylene rod (diameter 2 mm).…”
Section: Methodsmentioning
confidence: 99%